Experimental Study of The Use of Spiderman Game Media (Spinner of Education for Mankind) In Learning Sociology for Improving Student Learning Outcomes - Rusmiyati, Anna (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2020)
The aim of this research is to: (1) be able to vary the methods of learning in the classroom, (2) create fun and enjoyable learning by using spiderman games. That way it can make it easier to understand and comprehend learning material so that it improves student learning outcomes in sociology subjects at SMA Negeri 1 Pulung. This study uses a quasi experimental design method (quasi-experimental) with a form of nonequivalent control group design. The population in this study were students of class XI IPS (social science) 1 and XI IPS (social science) 3 of SMA Negeri 1 Pulung, totaling 68 students. The sample used in this study was the entire population, namely two classes from class XI of the IPS (social science) program. All class, divided to, one class is grouped into an experimental class (35 students) and another class as a control class (33 students). The experimental class applies the